2015
DOI: 10.1080/15374416.2015.1015135
|View full text |Cite
|
Sign up to set email alerts
|

Child-Directed Interaction Training for Young Children With Autism Spectrum Disorders: Parent and Child Outcomes

Abstract: This study examined the efficacy of the Child-Directed Interaction Training (CDIT) phase of Parent-Child Interaction Therapy for children with an Autism Spectrum Disorder (ASD). Thirty mother-child dyads with children ages 3-7 years with a diagnosis of ASD participated in this randomized controlled study. Following manualized CDIT, statistically significant and meaningful improvements in child disruptive behavior and social awareness as well as maternal distress associated with child disruptive behavior occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 21 publications
7
78
1
3
Order By: Relevance
“…Any changes in a child's behavior during an interaction with a parent must be considered in light of changes in parental behavior. Several studies confirm that the parent-child interaction is bi-directional--the child's behaviors impact the parent and vice versa (Ginn, Clionsky, Eyberg, Warner-Metzger, & Abner, 2015;Rutgers, Bakermans-Kranenburg, van Ijzendoorn, & van Berckelaer-Onnes, 2004;Siller & Sigman, 2008;Slaughter & Ong, 2014;Zhou & Yi, 2014). A recent parent-focused intervention study found that changes in ASD symptoms, as measured by the ADOS CSS, were mediated by parental synchrony (Pickles et al, 2015).…”
Section: Boscc 19mentioning
confidence: 96%
“…Any changes in a child's behavior during an interaction with a parent must be considered in light of changes in parental behavior. Several studies confirm that the parent-child interaction is bi-directional--the child's behaviors impact the parent and vice versa (Ginn, Clionsky, Eyberg, Warner-Metzger, & Abner, 2015;Rutgers, Bakermans-Kranenburg, van Ijzendoorn, & van Berckelaer-Onnes, 2004;Siller & Sigman, 2008;Slaughter & Ong, 2014;Zhou & Yi, 2014). A recent parent-focused intervention study found that changes in ASD symptoms, as measured by the ADOS CSS, were mediated by parental synchrony (Pickles et al, 2015).…”
Section: Boscc 19mentioning
confidence: 96%
“…PCIT has been found to be effective in reducing child externalizing behavior problems, as well as increasing child compliance, enhancing the parent child relationship, and reducing parenting stress [28,29]. In addition to children with externalizing behavior problems, PCIT and adaptations of PCIT have been shown to be effective with other at-risk child populations, such as children with early developmental or neurodevelopmental delays [30][31][32][33], anxiety [34][35][36], and depression [37,38]. PCIT also has been shown to be effective in increasing maternal sensitivity and positive interactions in parents at risk for maltreatment and abuse [39,40], as well as in children and families from ethnically and racially diverse backgrounds, such as Puerto Rican [41], Mexican-American [42,43], Alaskan native [44], Chinese [45], and Norweigan families [46] to name a few.…”
Section: Efficacy Of Pcitmentioning
confidence: 99%
“…The scale is widely used in studies of children with autism (e.g. Ginn et al, 2015;Sofronoff & Farbotko, 2002;Whittingham, 2009) and has been found to be sensitive to change following an intervention (Webster-Stratton & Hammond, 1997 indicates agreement with each item (1=strongly disagree to 6=strongly agree). Seven items are reverse coded so that a higher score represents increased parenting confidence.…”
Section: Outcome Measuresmentioning
confidence: 99%